Naravovarstveniki ali privrženci modnih smernic? - Petrova, Saska (Urbani izziv, 2009)
This paper focuses on the long-standing knowledge divide regarding urban dwellers' perceptions of, and attitudes towards, environmental management and protection in national parks in general and South Eastern Europe more specifically. The factors that lead contemporary tourists to visit such areas often remain unclear and inadequately connected to contemporary social science research. Therefore, we explore the profile and needs of urban visitors to the Pelister National Park in the Republic of Macedonia, with the aim of investigating the extent to which their motivation is driven by an intrinsic engagement with the natural features of the area itself, as opposed to a more superficial interest in its symbolic brand. The results of this paper, which lean towards the latter, emphasise the need for the development of an effective visitor management strategy as an integral part of the overall governance of national parks.
Keywords: environmental protection; fashion; Makedonija; moda; naravna dediščina; narodni parki; Republic of Macedonia; tourism; turisti; turizem; varstvo narave; življenjski stil